Analysis of the Beaufort Gyre Freshwater Content in 2003–2018. Issue 12 (28th December 2019) - Proshutinsky, A.; Krishfield, R.; Toole, J. M.; Timmermans, M.‐L.; Williams, W.; Zimmermann, S.; Yamamoto‐Kawai, M.; Armitage, T. W. K.; Dukhovskoy, D.; Golubeva, E.; Manucharyan, G. E.; Platov, G.; et al.
Abstract: Hydrographic data collected from research cruises, bottom‐anchored moorings, drifting Ice‐Tethered Profilers, and satellite altimetry in the Beaufort Gyre region of the Arctic Ocean document an increase of more than 6, 400 km 3 of liquid freshwater content from 2003 to 2018: a 40% growth relative to the climatology of the 1970s. This fresh water accumulation is shown to result from persistent anticyclonic atmospheric wind forcing (1997–2018) accompanied by sea ice melt, a wind‐forced redirection of Mackenzie River discharge from predominantly eastward to westward flow, and a contribution of low salinity waters of Pacific Ocean origin via Bering Strait. Despite significant uncertainties in the different observations, this study has demonstrated the synergistic value of having multiple diverse datasets to obtain a more comprehensive understanding of Beaufort Gyre freshwater content variability. For example, Beaufort Gyre Observational System (BGOS) surveys clearly show the interannual increase in freshwater content, but without satellite or Ice‐Tethered Profiler measurements, it is not possible to resolve the seasonal cycle of freshwater content, which in fact is larger than the year‐to‐year variability, or the more subtle interannual variations. Plain Language Abstract: The Beaufort Gyre centered in the Canada Basin of the Arctic Ocean is the major reservoir of fresh water in the Arctic. The primary focus of this study is on quantifying variability and trends in liquid (water) and solid (sea ice) freshwater content in this region. The Beaufort Gyre Exploration Program was initiated in 2003 to synthesize results of historical data analysis, design and conduct long‐term observations, and to provide information for numerical modeling under the umbrella of the FAMOS (Forum for Arctic Observing and Modeling Synthesis) project. The data collected from research cruises, moorings, Ice‐Tethered Profiler observations, and satellite altimetry document an increase of more than 6, 400 km 3 of liquid freshwater content from 2003 to 2018, a 40% growth relative to the climatology of the 1970s. This fresh water volume is comparable to the fresh water volume released to the sub‐arctic seas during the Great Salinity Anomaly episode of the 1970s. Thus, since the 2000s, the stage has been set for another possible release of fresh water to lower latitudes with accompanying climate impacts, including changes to sea ice conditions, ocean circulation, and ecosystems of the Sub‐Arctic similar to the influence of the Great Salinity Anomaly observed in the 1970s. Key Points: Beaufort Gyre freshwater content time series (2003–2018) from different data sets are updated, compared, and analyzed Qualitative and quantitative estimates of factors and mechanisms driving freshwater content changes are provided In 2003–2018, the major sources of accumulated fresh water were sea ice melt, Mackenzie River runoff, and Bering Strait transport